Análise dos atendimentos obstétricos realizados pelo SAMU de Botucatu, SP - Michelin, Nathallia Seródio [UNESP] (2015)
The general objective of the present study was to analyze the calls from the obstetric users of SAMU 192 in Botucatu, in 2012, as regards their pertinence and taking the women's parity into consideration. The present analytic and observational study included a population of women in the pregnancy-puerperium cycle as well as professionals of the primary healthcare network in the city of Botucatu, SP, Brazil. Data were collected from records of the Service and pertinent calls were all those resulting in referrals to hospitals and classified as red, orange and yellow according to the risk criteria proposed by the Brazilian Ministry of Health. As regards the involved professionals, the study sample comprised 67 peoples including physicians, nurses, nursing assistants/technicians and community healthcare agents. The chi-square, Kruskal-Wallis and exact Fisher's tests were utilized in the statistical analyses, and the critic p value was set at <0.05. The analyses were performed with the SPSS v15.0 software. The present study was approved by the Committee for Ethics in Research of Faculdade de Medicina de Botucatu - UNESP. A low prevalence of non pertinent demand was observed as both classification criteria were considered. No statistically significant difference was observed in relation to the non pertinent demand as the women's parity was considered. As the different professional categories involved in primary healthcare activities were considered, no difference was observed in the degree of priority given by SAMU to primiparae and multiparae. The scoring of the professionals' knowledge about demand pertinence ranged between 7 and 8 and may be considered high. The excellent health conditions of the women at their admission, their mild complaints and the reporting of mild findings by the professionals suggest that the index of referrals to the reference center might be overestimated, indicating lack of integration between primary ...